Lithium Modulates Autophagy in Esophageal and Colorectal Cancer Cells and Enhances the Efficacy of Therapeutic Agents In Vitro and In Vivo - O’Donovan, Tracey R.; Rajendran, Simon; O’Reilly, Seamus; O’Sullivan, Gerald C.; McKenna, Sharon L. (PLOS ONE, 2015)
Many epithelial cancers, particularly gastrointestinal tract cancers, remain poor prognosis diseases, due to resistance to cytotoxic therapy and local or metastatic recurrence. We have previously shown that apoptosis incompetent esophageal cancer cells induce autophagy in response to chemotherapeutic agents and this can facilitate their recovery. However, known pharmacological inhibitors of autophagy could not enhance cytotoxicity. In this study, we have examined two well known, clinically approved autophagy inducers, rapamycin and lithium, for their effects on chemosensitivity in apoptosis incompetent cancer cells. Both lithium and rapamycin were shown to induce autophagosomes in esophageal and colorectal cancer cells by western blot analysis of LC3 isoforms, morphology and FACS quantitation of Cyto-ID or mCherry-GFP-LC3. Analysis of autophagic flux indicates inefficient autophagosome processing in lithium treated cells, whereas rapamycin treated cells showed efficient flux. Viability and recovery was assessed by clonogenic assays. When combined with the chemotherapeutic agent 5-fluorouracil, rapamycin was protective. In contrast, lithium showed strong enhancement of non-apoptotic cell death. The combination of lithium with 5-fluorouracil or oxaliplatin was then tested in the syngenic mouse (balb/c) colorectal cancer model—CT26. When either chemotherapeutic agent was combined with lithium a significant reduction in tumor volume was achieved. In addition, survival was dramatically increased in the combination group (p < 0.0001), with > 50% of animals achieving long term cure without re-occurrence (> 1 year tumor free). Thus, combination treatment with lithium can substantially improve the efficacy of chemotherapeutic agents in apoptosis deficient cancer cells. Induction of compromised autophagy may contribute to this cytotoxicity.